تجربة مركز تنمية العلوم واللغات بجامعة السّلطان الشّريف عليّ الإسلاميّة في تعليم اللّغة العربيّة للنّاطقين بغيرها: دراسة وصفية تحليلية: برنامج اللغة العربية، تعليم اللغة العربية لغير الناطقين بها - Ø³Ø¨ÙˆØ¹ÙŠ, ØµØ§Ù„Ø (Al-Ḍād Journal, 2018)
This study aims to introduce the experience of Sultan Sharif Ali Islamic University (UNISSA) in Brunei Darussalam in teaching Arabic language to Non- Arabic speakers; by presenting the experience of the Centre for the Promotion of Knowledge and Languages (CPKL) at this university. This experience is presented through the age of this experience, its contents, objectives and the most important methods and programs adopted in achieving the objectives of this experience and its success. The main findings of this descriptive analytical study are; the Center's experience in teaching Arabic is a pioneering experience in its field compared to the period of the university's establishment, which did not exceed a decade. The study also concluded that the teaching of Arabic language at CPKL has contributed significantly to the achievement of the University's mission and objectives in teaching the Arabic language, which supported the expectations of His Majesty the Sultan Haji Hassan al-Bolkiah to make Brunei Darussalam a state of Zikir (remembrance); by encouraging the teaching and learning of the Arabic language. The study also confirmed that the Centre by its pilot experience has been able to provide valuable opportunities for local students from the public to learn the language of the Holy Quran and providing to them a large number of relevant references in the field of teaching Arabic.